Performance evaluation of a fog computing solution for smart health environments - Vilela, Pedro Henrique (2019)
Cloud computing has been a predominant approach for the development of Internet of Things (IoT) solutions. However, to meet the requirements of real-time and latencysensitive applications in healthcare, a new computing paradigm that follows a cloud computing approach, called fog computing, demonstrates to be an effective tool by extending the cloud resources to the edge of the network. This work studies the contribution of the fog computing paradigm applied to healthcare, highlighting its main benefits regarding latency, network usage, and power consumption. Based on these parameters, a fog-assisted health monitoring system is proposed, and its performance evaluation and demonstration are carried out. The results demonstrate the potential enhancement of this approach in minimising data traffic in the core of the network because data is locally analysed. Further, it improves security and privacy of sensitive health information, once the data is kept in the local premises.